Ergothioneine Antioxidant Function: From Chemistry to Cardiovascular Therapeutic Potential. Issue 4 (April 2017) - Servillo, Luigi; D'Onofrio, Nunzia; Balestrieri, Maria Luisa
Abstract : Abstract: Ergothioneine (ESH), the betaine of 2-mercapto-L-histidine, is a water-soluble naturally occurring amino acid with antioxidant properties. ESH accumulates in several human and animal tissues up to millimolar concentration through its high affinity transporter, namely the organic cation transporter 1 (OCTN1). ESH, first isolated from the ergot fungus ( Claviceps purpurea ), is synthesized only by Actinomycetales and non-yeast–like fungi. Plants absorb ESH via symbiotic associations between their roots and soil fungi, whereas mammals acquire it solely from dietary sources. Numerous evidence demonstrated the antioxidant and cytoprotective effects of ESH, including protection against cardiovascular diseases, chronic inflammatory conditions, ultraviolet radiation damages, and neuronal injuries. Although more than a century after its discovery has gone by, our understanding on the in vivo ESH mechanism is limited and this compound still intrigues researchers. However, recent evidence about differences in chemical redox behavior between ESH and alkylthiols, such as cysteine and glutathione, has opened new perspectives on the role of ESH during oxidative damage. In this short review, we discuss the role of ESH in the complex machinery of the cellular antioxidant defense focusing on the current knowledge on its chemical mechanism of action in the protection against cardiovascular disease.